Public Administration and Local Government in coronavirus crisis - Mouroutsos, Ioannis (HAPSc Policy Briefs Series, 2020)
This policy brief presents the necessary measures taken by the government in cooperation with other state bodies to deal with the health crisis in the field of public and local administration. The policy brief highlights some of the major changes that have been attempted for the digital state and the integration of new technologies into our daily lives as well as their usefulness in a range of activities utilized across the spectrum of public administration, from the narrow public sector to the first and second degree administration.